Pemberdayaan Kader Kesehatan Masyarakat dengan Menggunakan Ular Tangga Sebagai Media Health Promotion: Empowerment of Public Health Cadres by Using Snakes and Ladders as Health Promotion Media - Nutrisia Nu'im Haiya; Iwan Ardian (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Diarrhea is the cause of high mortality and morbidity in children, which is caused by various factors, especially low public awareness and the ability of children to wash their hands, are causes that must be controlled by increasing knowledge. One way to increase knowledge among the Indonesian people with a large population is through empowering health cadres as agents of change, but the dynamics show that health cadres are still unfamiliar with various health promotion media, and Snakes and Ladders media is an effective medium for increasing children's knowledge; therefore empowerment is needed to health cadres. Initiating the empowerment of health cadres to carry out health promotion using snakes and ladders media is a method that can be used because health cadres are the closest part of the community, so that they can reach the community, and games are the suitable media for children. The result of this service is an increase in the knowledge and ability of cadres about health promotion with Snakes and Ladders media. Health cadres are formed who can carry out health promotion using Snakes and Ladders media. There is an increase in children's knowledge and abilities about how to wash their hands with soap. With a sustainable program, the ability to wash hands can continue to increase and prevent the occurrence of diarrheal diseases or various other diseases so that Indonesia's health status increases.